SISTEM INFORMASI PENDATAAN DAN PENJUALAN BERAS STUDY KASUS RUKUN JAYA - alfiah, nurul; Salsabila, Khusna (STMIK Komputama Majenang, 2021)
Technological developments continue to move forward in an effort to facilitate a more effective and efficient work system. Rukun Jaya is a rice mill and rice sales business that requires information system technology in the process of managing its business. Data collection of goods that is still done manually is often an obstacle in the Rukun Jaya rice milling business. This causes the work system to be unstructured so that it becomes a waste of energy. This problem affects the estimation of decision making on the sale of goods. In determining the number of goods per production, if inventory checks are not carried out in the warehouse, it will be difficult to plan for the availability of goods in the future. Desktop application designed using MySQL and Microsoft Visual Studio Net. Facilities that can be in the form of admin data management, admin data processing, customer data, goods data, sales transactions and sales reports. The result of this information system design is a successful desktop application to facilitate Rukun Jaya owners in data collection and rice sales transactions